Intelligent grids for faster elemental mapping with Laser-induced breakdown spectroscopy - Capela, Diana; Ferreira, Miguel; Lima, Alexandre; Jorge, Pedro; Guimarães, Diana; Silva, Nuno A. (Results in optics, 2023)
Laser-induced breakdown spectroscopy is a spectroscopic technique that allows for fast elemental mapping of heterogeneous samples. Yet, detailed maps need high-resolution sampling grids, which can turn the task into a time-consuming process and can increase sample damage. In this work, we present the implementation of an imaged-based intelligent mesh algorithm that makes use of superpixel segmentation to optimize elemental mapping processes. Our results show that the approach can increase the elemental mapping resolution and decrease acquisition times, fostering opportunities for applications that benefit from minimal sample damage such as heritage analysis, or timely analysis such as industrial applications.